2017
DOI: 10.1681/asn.2016070775
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Systemically Administered Human Muse Cells in Adriamycin Nephropathy

Abstract: Multilineage-differentiating stress-enduring (Muse) cells are nontumorigenic endogenous pluripotent-like stem cells that can be collected from various organs. Intravenously administered Muse cells have been shown to spontaneously migrate to damaged tissue and replenish lost cells, but the effect in FSGS is unknown. We systemically administered human bone marrow-derived Muse cells without concurrent administration of immunosuppressants to severe combined immune-deficient (SCID) and BALB/c mouse models with adri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 42 publications
3
76
0
Order By: Relevance
“…Reactive astrocytes are an important therapeutic target of ALS 29 , and the microenvironmental signal of the ALS mice spinal cord may differentiate Muse cells into GFAP-positive astrocytes, especially into A2 astrocytes, which might secrete molecules that provide neurotrophic support and modulate inflammatory responses 30 . Muse cells themselves can produce various neurotrophic factors, including brain-derived neurotrophic factor (BDNF), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), insulin-like growth factor 1 (IGF-1), epidermal growth factor (EGF), prostaglandin E2 (PGE2), and angiopietin-1 (Ang1) [16][17][18][19]31 . Therefore, they might have supplied beneficial factors to motor neurons and astrocytes, preventing myofiber atrophy in the ALS model.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrocytes are an important therapeutic target of ALS 29 , and the microenvironmental signal of the ALS mice spinal cord may differentiate Muse cells into GFAP-positive astrocytes, especially into A2 astrocytes, which might secrete molecules that provide neurotrophic support and modulate inflammatory responses 30 . Muse cells themselves can produce various neurotrophic factors, including brain-derived neurotrophic factor (BDNF), hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), insulin-like growth factor 1 (IGF-1), epidermal growth factor (EGF), prostaglandin E2 (PGE2), and angiopietin-1 (Ang1) [16][17][18][19]31 . Therefore, they might have supplied beneficial factors to motor neurons and astrocytes, preventing myofiber atrophy in the ALS model.…”
Section: Discussionmentioning
confidence: 99%
“…Muse cells (multilineage differentiating stress enduring cells) are a group of multipotent stem cells identified from 3D culture of bone marrow stromal cells that could be differentiated into multiple lineages in vitro and in vivo (20). Although it is still highly controversial due to the lack of in vivo identities (21), the isolation (21) and application of muse cells in animal disease models are well documented from multiple laboratories (22)(23)(24). These evidences indicated that the 3D culture system used in muse cells identification might be stromal stem cell supportive, which makes it attractive to use in our primary DPC culture to test whether there are previous undocumented stem cells in dental papilla.…”
Section: Cells From Mouse Dental Papilla Could Initiate Sphere Formatmentioning
confidence: 99%
“…Regarding feasibility for clinical applications, an approximately 30 mL volume of human bone marrow (BM) aspirate yields 1 million Muse cells by day 3 7 . In recent studies involving animal models of muscle damage 8 , stroke 13 , liver damage 14 , 15 , and chronic kidney disease 16 , intravenously or locally injected Muse cells actively migrated to and preferentially engrafted into damaged tissues, spontaneously differentiated into tissue-compatible cells in response to the microenvironment, and facilitated structural and functional recovery 8 . Recent publications also reported that the trophic effects of Muse cells facilitated tissue repair in animal models of diabetes mellitus–related skin ulcers 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%